Vaccine Narratives on Telegram: A Data-Driven Study of Information Diffusion in Brazil - Oliveira, Fernando H. M. de; Rodrigues, Cleyton Mário de O. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2026.25323, 2026)
This study analyzes over 330,000 vaccine-related Telegram messages in Brazil (2020–2025) to investigate diffusion dynamics. Results show that diffusion is strongly associated with message exposure, with visibility dominating observed engagement patterns. Forwarding is consistently associated with higher redistribution and reach, while user reactions show limited association with propagation. Contrary to common assumptions, content volume and user activity are not consistently linked to higher engagement outcomes. These findings highlight Telegram’s broadcast-like dynamics providing insights into large-scale information spread in low-moderation environments, and offering empirical support for public health strategies.